Catchment zoning to enhance co‐benefits and minimize trade‐offs between ecosystem services and freshwater biodiversity conservation. Issue 4 (30th March 2018) - Hermoso, Virgilio; Cattarino, Lorenzo; Linke, Simon; Kennard, Mark J.
Abstract: Integrating ecosystem services (ESs) in landscape planning can help to identify conservation opportunities by finding co‐benefits between biodiversity conservation and the maintenance of regulating and cultural ecosystem services. The adequate integration of ESs needs careful consideration of potential trade‐offs, however, especially between provisioning services and biodiversity conservation (e.g. the potentially negative consequences of agricultural water extraction within areas important for the maintenance of biodiversity). These trade‐offs have been overlooked in systematic spatial planning to date, especially in freshwater systems. marxan with zones was used to identify priority areas for the conservation of freshwater biodiversity (139 species of freshwater fish, turtles, and waterbirds) and the provision of freshwater ESs in the Daly River, northern Australia. Four different surrogates for ESs were mapped, including those potentially incompatible with conservation goals (i.e. groundwater provision for agriculture and recreational fisheries) and those that are more compatible with conservation (i.e. flood regulation by riparian forests; provision of perennial water). The spatial allocation of multiple management zones was prioritized: (i) three conservation zones, aiming to represent freshwater biodiversity and compatible ESs to enhance co‐benefits; and (ii) two production zones, where access to provisioning ESs could be granted. The representation of ESs obtained when using the multi‐zoning approach was compared with that achieved with a single management zone approach. The comparison was performed across different representation targets. Different results were found with low and high targets for ESs. With low targets (<25% of all ESs), the multi‐zoning approach achieved up to 53% more co‐benefits than the single‐zone approach. With high targets (>25% of all ESs), the trade‐offs avoided were more evident, with up to 56% less representation of incompatible ESs within conservation zones. Multi‐zone planning could help decision makers respond better to the increasingly complex catchment management context, caused by an increasing demand for provisioning services and a diminishing availability of resources, as well as manage and plan for challenges in other realms facing similar problems.